0365 Estimation of the burden of chronic obstructive pulmonary disease due to occupation in great britain. (21st August 2017) - Hutchings, Sally; Rushton, Lesley; Sadhra, Steven; Fishwick, David
Abstract : Introduction: We have estimated the burden of COPD for deaths and prevalence due to occupational exposures in Britain using published literature and available national data plus a population based job exposure matrix (ACEJEM). The prevalence estimate avoids underestimation of the burden as estimates of COPD deaths, or hospitalisations, only account for the most serious cases. Methods: We used population attributable fractions (PAFs), requiring estimates of the population exposed to airborne pollutants at work, derived from 2001 Census data by job code matched to a JEM giving proportions exposed and average levels of exposure to pollutants including vapours, gases, dusts, fumes (VGDF) by UK SOC2000 job code. Exposures were matched to the best currently available population-based risk estimates. We estimated prevalent COPD PAFs using a novel age-time window approach to estimate prevalent numbers exposed, and deaths from COPD which requires numbers ever exposed were estimated using a risk exposure period methodology, taking into account age. Results: The PAF for prevalent COPD due to occupational exposure to VGDF was 18.7% for men, 8.0% for women and 11.5% overall giving 22 700 cases in men and 13 400 in women. Equivalent PAFs for COPD deaths, based on exposure 30+ years before 2010, were 18.3%/6.1%/12.3% (2, 480 deaths in men, 790 in women). Prevalent PAF estimates which included a 30 year onset lag and mortality PAFs assuming 0–80 year latencies produced very similar results. Conclusions: The novel approach, making best use of available data, provides burden estimates which may inform strategies for reducing workplace COPD risks.